DESENVOLVIMENTO REGIONAL E AGRICULTURA: Uma análise da sojicultura na microrregião de Chapadinha - MA - FREITAS, Caio Guimarães de (2022)
The theme of regional development is particularly important in a country that faces great inequalities and with large territorial dimensions such as Brazil. In this sense, the search for paths that lead peripheral territories to a development trajectory becomes crucial to deal with the current scenario. At the national level, there are those who defend the idea that Brazilian agribusiness is a good alternative for development, since the agricultural-export model would be a “natural vocation of Brazil”. However, there are also those who point out the infeasibility of this sector to lead the development of a territory. The present work analyzes the case of soybean agriculture in the micro-region of Chapadinha - MA and whether this activity would have the potential to trigger a process of development in the territory. For this, some theories of classical authors of development such as Perroux, Myrdal, Hirschman and North are approached. For a better historical contextualization of the micro-region, a brief historical incursion into the process of economic formation of the state of Maranhão is made, pointing out the emergence and trajectory of some activities of great representation in contemporary economic dynamics, among them soybean agriculture. It also discusses how soybean farming in the micro-region is part of a global logic that relegates the activity of supplying commodities to the dynamic centers of world capitalism to the periphery of the system. The research results showed that in the period of rise of soybeans agriculture in the micro-region of Chapadinha there was a loss of relevance of the agricultural sector in the economic activity of the territory. Soybean farming also showed a very low capacity to incorporate labor. In the analyzed period, it was in fact the public sector that presented greater relevance for the local economic activity and that obtained better results in the incorporation of labor in the micro-region. It was observed, therefore, that as the literature on the subject points out, soybean agriculture in the Chapadinha micro-region is an economic enclave with a low potential to generate productive chains capable of encouraging development in the territory, in addition to presenting an excluding character for the rural sector.